4D food printing - Chen, Marian Li-Qin (Nanyang Technological University, 2021)
This final year report aims to show the rheological properties of the fabricated food ink samples made from tapioca starch or rice flour to water mixture. Organic anthocyanin-rich purple corn powder was then used to investigate the effects of an external stimulus such as pH. Hydrocolloids were not added to the food ink mixture. The rheological properties of the food ink mixture were measured using a rheometer. The rheological study results and analysis shows how the different combinations of base material to water mixture with an added amount of anthocyanin affect the rheological properties of the food ink. A steady-state flow ramp experiment was performed to understand the shear-thinning or thickening properties of the various fabricated food ink samples. To test for shape printability, star-shaped polygon test structures were used while an octopus was used to test the printing accuracy of selected optimized food ink samples. To fabricate a 4D product, the 3D printed food samples were then sprayed with different pH solutions using ingredients such as sodium bicarbonate and lemon juice. A controlled pH change was carried out, and the time required for this pH change was characterized. The colour changes were assessed and examined.